CORRELATION BETWEEN VOCABULARY MASTERY AND READING COMPREHENSION - Enjel Enjel; Darmawan Darmawan; Mashuri Mashuri (e-Journal of ELTS (English Language Teaching Society), 2022)
The purpose of this research is to find out if there is any significant correlation between vocabulary mastery and reading comprehension of the eighth-grade students of SMP Negeri 32 Sigi. A correlational research design was used in this research and applied quantitative approach. The researchers used a simple random sampling technique to choose the sample. 36 students were chosen as the sample in this research. The researchers collected data using tests as the primary instrument, which included a vocabulary and reading test. The average score of the vocabulary test was 85 and the reading comprehension test was 80. It revealed that two variables have positive relationship. The Pearson Product Moment result of both tests' data analysis was 0.539. The category was moderate. The value of rtable was 0.329 when the degree of freedom (df) was 36 and the level of significance was 0.05. According to the data, rxy is higher than rtable. It can be concluded that alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. This indicates that there is a positive and significant correlation between the vocabulary mastery and reading comprehension of the eighth-grade students of SMP Negeri 32 Sigi.